(untitled) (American Journal of Energy and Natural Resources, 2024)
Nigeria is the most populous country in the Organization of Petroleum Exporting Countries (OPEC) with a population of about 250 million people. Bauchi metropolis has witnessed great changes in recent years, in terms of population growth and rapid urbanization. This study aims to assess the level of compliance of petrol filling stations in Bauchi metropolis to the standards of the Department of Petroleum Resources [DPR] (2007) and Bauchi State Development Board [BSDB] (2012) guidelines. Field survey, Grid3 portal and Global positioning system (GPS) were the research instruments used for the study. ArcGIS 10.8 was used to carry out the analysis using the Buffer and Near analyses. The results indicated that the distribution pattern of the filling stations is clustered. The study found out that only 33.63% of the stations violated the criterion of a 15-meter minimum distance from the road while the rest fulfilled that requirement. However, 11.81% of the stations met a minimum distance of 400 meters from their nearest neighbors, while 88.18% failed to achieve the minimum distance of 400 meters. The study also revealed that only 3.63% met the requirement of not more than four stations within a 2 Km radius. Based on the findings of this research, the study recommends that the DPR and the BSUDB should create a database for filling stations in Bauchi Metropolis.